POTENSI RISET MASA DEPAN DALAM KONTEKS RIBA - Majduddin, Muhammad; Nadjib, Muhammad; Asnawi, Nur; Farid, Muhammad; Danila, Nevi (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This paper investigates the changing function of digital zakat inside Islamic social finance and emphasizes its ability to solve economic inequity and poverty in environments with a majority of Muslims. While zakat systems are fundamental to social justice, conventional management approaches struggle with inefficiency, lack of openness, and low public confidence. Digital technologies include blockchain, artificial intelligence, and integrated zakat platforms provide interesting answers with the rise of financial technology, but need appropriate alignment with maqashid al-shariah and governance systems to guarantee ethical outputs. This study maps important theme trends, methodological developments, and current research gaps in digital zakat studies utilizing a Systematic Literature Review (SLR) paired with bibliometric analysis. The results highlight the need for inclusive, data-driven, sharia-compliant digital zakat systems that strike a balance between social and ethical issues and technical developments. This paper offers both theoretical analysis and pragmatic suggestions for improving responsible zakat administration